PENGARUH PENGGUNAAN PROBLEM BASED LEARNING (PBL) DAN CONTEXTUAL TEACHING LEARNING (CTL) TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI MINAT BELAJAR (Studi Eksperimen pada Peserta didik Kelas VI SDN Jebres Surakarta) - Sumarmi, Dw (JURNAL SINEKTIK, 2023)
The of this study istodescribe the use ofthe ProblemeBasedeLearningemodel and the ContextualeTeaching Learninge model which is reviewed from the interest in learning in grade VI students of SDN Jebres Surakarta District.  "This research is classified as a pseudo-experimental study carried out from August to December 2019. This study used afactorial essay d 2 X 2. The sampling technique uses proportional cluster sampling.  The schools used for the research were class VI students at SDN Petoran as many as 31 students and Mijen as many as 20 students in the Surakarta area. The research instruments used are tests to measure learning outcomes and questionnaires for learning interests. Data analysis used equilibrium test, pre-treatment, two-way ANAVA test, and double compensatory test. The results of the study are 1) The results of learning mathematics using the ProblemeBased Learning model are better than using  the ContextualeTeaching Learning model  on the subject matter of mixed fractional number operations.  2) The mathematics learning outcomes of students who have a high level of interest in learning are better than students who have a low level of interest in learning on the subject matter of mixed fractional number operations. 3) There is an interactionebetween the learning modeleandethe level of student learning interestetowards the outcome of "learning mathematics materialeoperation numberemixed fractions.